Tajaliyyāt al-Ta’āyus al-Mushtarak fī al-Shi’ri al-Arabi al-Mu’asir, Dirāsah Mauduiyah - MAIGA, Mohamadou Aboubacar (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2024)
Coexistence is one of the concepts that has received significant attention in light of contemporary societal changes to achieve the stability of societies and the coexistence of its members in harmony and peace, in addition to its importance at the level of relations between countries. From these starting points, this research aims, through the use of the descriptive analytical method, to shed light on literary texts from the contemporary era that call for coexistence and seek to clarify the elements that unite people and do not separate them based on race or sect. The research tries to answer the following questions: What is the concept of coexistence? What are the images of coexistence in contemporary Arabic poetry? Who are the most important poets who have employed the values of coexistence in their literary works? The first chapter deals with coexistence, its foundations, principles, components, and fruits. The second chapter deals with the patterns of coexistence in contemporary Arabic poetry. It is worth noting that a follower of the texts of contemporary Arabic literature sees the value of coexistence present in various forms and images presented by writers in a way that agrees with their creativity and artistic vision, directly or implicitly. Literary texts play a significant role in establishing human concepts to ensure the establishment of the language of fruitful dialogue and the achievement of cultural and civilizational coexistence between human societies.